A Study of Status for Teamwork of Personnel in educational institutions Mueangmai Group Under Phichit Primary Educational Service Area Office 1 - Kijja, Nutthakan; Natun, Jaruwan (Academic MCU Buriram Journal, 2025)
The purpose of this research was to study of status for teamwork of personnel in educational institutions Mueangmai group under Phichit primary educational service area office 1. We used the entire population as a sample for the study.13 school administrators and teachers 68 people. By selecting a specific person, including all informants amount 81 person. The tool used in the research was a questionnaire on the status for teamwork of personnel in educational institutions Mueangmai group under Phichit primary educational service area office 1. This is an approximate scale 5 level. This questionnaire has a conformance index (IOC) is 1.00 and the confidence value of the questionnaire is 0.954. The statistics used in the data analysis are: Frequency, Percentage average and standard deviation. The research results found that: The status for teamwork of personnel in educational institutions Mueangmai group under Phichit primary educational service area office 1 was at a high level. When looking at each side, it was found that the aspect with the highest average value was the aspect of building mutual trust. Next is participation, which is at a high level. And the side with the lowest average value is the side of having the same goal.